Analisis Biaya dan Tingkat Layanan Sistem Antrian Call Center Menggunakan Model M/M/S: Penelitian - Nerli Khairani; Rizky Suhaila Hsb; Septika Aulia Putri; Sesy Ophelia Tampubolon (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze cost optimization and service level in a call center queueing system using the M/M/S model. The main problem addressed is the imbalance between operational cost efficiency and customer service quality in determining the optimal number of servers. The research applies a quantitative approach with a case study design based on 1,251 historical observations of call center performance. Data were analyzed using the M/M/S queueing model with arrival and service rate parameters of 8.27 customers per hour and 22.85 customers per hour per server, respectively. The results indicate that the two-server configuration is the optimal solution, achieving a 96.8% service level and an operational cost of Rp 56,601 per hour, meeting industry standards while maintaining cost efficiency. This configuration yields a 45.3% improvement in service level compared to one server with a 61.8% cost increase, while adding a third server provides only marginal improvement. The findings provide practical implications for call center management in balancing financial and service quality aspects. In addition, this study offers educational value as a learning resource in applied mathematics and operations research courses.